The Effects Of Bursa Malaysia Berhad’s 2018 Sustainability Reporting Guide And Assurance On Corporate Reporting And Firm Value - Awad, Bakry Ahmed Elsayed (2023)
This study aims to examine the impact of these amendments on three characteristics of CSRR and explore the moderating role of CSRR assurance on this effect across a sample of companies from the largest 100 companies by market capitalization during the period of 2017-2020. It also seeks to examine whether investors value the change in CSRR caused by the implementation of these new initiatives to determine whether CSRR meets the expectations of stakeholders.